Affective and cognitive theory of mind in posttraumatic stress, major depressive, and somatic symptom disorders: association with childhood trauma - Seitz, Katja I.; Ehler, Nicola; Schmitz, Marius; Schmitz, Sara Elena; Dziobek, Isabel; Herpertz, Sabine; Bertsch, Katja (The British journal of clinical psychology, 2022)
Objectives Childhood trauma constitutes a major risk factor for adult psychopathology, including posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and somatic symptom disorder (SSD). One potential mechanism linking childhood trauma to adult psychopathology may be alterations in theory of mind (ToM). Given the lack of transdiagnostic studies on the association between childhood trauma and ToM, further research is needed to elucidate whether and how childhood trauma relates to ToM impairments across and within diagnostic boundaries. Design A cross-sectional study design was applied. Methods A total of 137 individuals with varying levels of childhood trauma took part in this study, encompassing individuals with PTSD (n = 33), MDD (n = 33), SSD (n = 36), and healthy volunteers (HVs; n = 35). To assess ToM performance and childhood trauma, the Movie for the Assessment of Social Cognition was administered along with the Childhood Trauma Questionnaire. Results Only individuals with PTSD, but not individuals with MDD or SSD, showed a worse ToM performance compared to HVs. In the whole sample, childhood trauma correlated negatively with ToM performance. Exploratory group-specific analyses revealed higher levels of childhood trauma to be associated with more excessive ToM errors in individuals with SSD, and notably with an enhanced ToM performance in individuals with MDD. Conclusions Our results indicate associations between childhood trauma and ToM impairments in a large, transdiagnostic sample. Provided replication in future studies, our findings suggest ToM capacities as a promising treatment target for individuals exposed to severe childhood trauma, at least or particularly with a diagnosis of PTSD. Practitioner points Our results suggest that individuals with a history of severe childhood trauma, at least or particularly with a clinical diagnosis of posttraumatic stress disorder, may benefit from therapeutic approaches targeting theory of mind capacities. Our findings indicate that higher levels of childhood trauma may be linked to a specific ‘hypermentalizing’ bias in somatic symptom disorder. Our findings further point towards an association between higher levels of childhood trauma and a heightened - rather than a diminished - sensitivity towards interpersonal cues in major depressive disorder. Provided further confirmatory evidence, our findings may support diagnosis-specific approaches in ameliorating theory of mind abilities in individuals with different mental disorders and a history of severe childhood trauma.